A hybrid method to deformation force of high-speed cold roll-beating forming - Yang, M.-S.; Li, Y.; Yuan, Q.-L. (Journal of Digital Information Management, 2013)
High-speed cold roll-beating forming technique is a new near-net plastic forming method that the intermittent high-speed roll-beating is used to achieve dynamic impact local loading, and that is fast, transient, high impact, large deformation of the complex forming process. For this forming process, the main stress method is employed to derive an analytic formula for the deformation force. Taking into account the main stress method can not reflect impact factors such as high-speed transient roll beating in process of this analytic solution, then the ABAQUS/Explicit is applied to simulate for highspeed cold roll- beating. The regression analysis is used to correct for the analytic formula based on simulation results, which makes the analytic formula more accurate reflection of deformation force of the different technological parameters of high-speed cold roll-beating. The forming experiments are carried out with self developed high-speed cold roll-beating experimental equipment and the experimental of deformation force is measured to verify the correctness of the corrected analytic formula.
Keywords: Cold roll-beating; Deformation force; Experimental verification; Slab method